2021
DOI: 10.1097/md.0000000000026639
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pneumatic compression for prolonged standing workers with leg edema and pain

Abstract: Even healthy individuals often encounter leg venous symptoms such as heaviness, pain, and swelling especially after prolonged standing work. Intermittent pneumatic compression (IPC) is a widely used simple therapy for preventing deep vein thrombosis and for treating lymphedema and chronic venous insufficiency. However, IPC has not been evaluated for its effect in relieving venous symptoms of healthy people. This was single center, cross-over study to investigate the effect of IPC for 20 healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…A previous study of people without any specific vascular diseases or symptoms with prolonged standing occupations reported that the ankle hydrostatic venous pressure increased to 90 mmHg and leg volume deteriorated to 50 mL when standing for a long time [ 30 – 33 ]. Similar to previous studies, this study confirmed that prolonged standing work causes leg pain and swelling [ 2 5 , 24 , 30 34 ]. In protocol A and C where stockings were not worn, the mean leg volume at T1 compared to that at T0 increased by 65.4–81.1 mL, and the circumference increased by 0–0.1 cm in the distal area below the calf and clearly increased by 0.1–0.4 cm in the proximal area.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A previous study of people without any specific vascular diseases or symptoms with prolonged standing occupations reported that the ankle hydrostatic venous pressure increased to 90 mmHg and leg volume deteriorated to 50 mL when standing for a long time [ 30 – 33 ]. Similar to previous studies, this study confirmed that prolonged standing work causes leg pain and swelling [ 2 5 , 24 , 30 34 ]. In protocol A and C where stockings were not worn, the mean leg volume at T1 compared to that at T0 increased by 65.4–81.1 mL, and the circumference increased by 0–0.1 cm in the distal area below the calf and clearly increased by 0.1–0.4 cm in the proximal area.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the findings of this study confirmed that IPC can effectively treat leg pain and edema in people with occupations requiring prolonged standing. Although several studies have reported on the effectiveness of IPC and MCS in people who were standing for a long time or patients with venous insufficiency, this study contained several unique issues [ 6 , 15 18 , 21 , 24 , 34 ]. First, this study targeted people who had an 8 h standing occupation rather than a short standing or sedentary occupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy legs was a common symptom in manual and standing workers participating in our study. Very few publications address the association between this symptom and occupational activity, despite the fact that working conditions such as prolonged standing promote venous disorders [ 55 ]. The problem of prolonged standing also affects manual workers as proven by a 2019 study on the relationship between static standing time at work and the intensity of pain in the lower extremities [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…При статичних навантаженнях ППК краще, ніж пасивний відпочинок, зменшує біль у нижніх кінцівках [17]. Існує розбіжність щодо того, чи впливає ППК на біль, викликаний спортивними навантаженнями.…”
unclassified